2014
DOI: 10.3121/cmr.2013.1171
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Physical Activity Program Use Among Older Adults

Abstract: Objective: Regular physical activity (PA) is important for maintaining long-term physical, cognitive, and emotional health. However, few older adults engage in routine PA, and even fewer take advantage of programs designed to enhance PA participation. Though most managed Medicare members have free access to the Silver Sneakers and EnhanceFitness PA programs, the vast majority of eligible seniors do not utilize these programs. The goal of this qualitative study was to better understand the barriers to and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
261
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(294 citation statements)
references
References 52 publications
26
261
2
5
Order By: Relevance
“…In an attempt to understand physical activity changes during older adulthood, researchers have focused on identifying barriers and facilitators to exercise participation (Bethancourt et al 2014). In their study, Bethancourt et al (2014) found that for older adults, barriers to physical activity participation included poor health, lack of professional guidance, and inadequate dissemination of information on available programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to understand physical activity changes during older adulthood, researchers have focused on identifying barriers and facilitators to exercise participation (Bethancourt et al 2014). In their study, Bethancourt et al (2014) found that for older adults, barriers to physical activity participation included poor health, lack of professional guidance, and inadequate dissemination of information on available programs.…”
mentioning
confidence: 99%
“…In their study, Bethancourt et al (2014) found that for older adults, barriers to physical activity participation included poor health, lack of professional guidance, and inadequate dissemination of information on available programs. They identified several facilitators of exercise participation including motivation to maintain physical and mental health and access to stimulating and accessible physical activity programs.…”
mentioning
confidence: 99%
“…Outra pesquisa qualitativa desenvolvida em Washington envolvendo sujeitos entre 66 e 78 anos identificou como principal barreira para o desenvolvimento de atividade física regular, limitações físicas decorrentes de problemas de saú-de ou envelhecimento. Ainda, concluiu que a falta de orientação profissional e ausência de orientação sobre programas de treinamento adequados estavam associados com os níveis de adesão 25 . Esperava-se encontrar maior prevalência de atividade física em indivíduos com maior renda familiar.…”
Section: Introductionunclassified
“…One of the many reasons for this is because many individuals ≥50 years are physically inactive and do not meet the national guidelines for PA [5]. Motivation of older adults to participate in PA has been studied by many researchers [2,9,12,45,53,54]; however, limited research has been done on motivation as part of technology facilitation for older adults' PA.…”
Section: Motivation For Physical Activitymentioning
confidence: 99%